PENGARUH WAKTU SETELAH PENYEMBELIHAN AYAM AFKIR TERHADAP KARAKTERISTIK BAKSO DENGAN FILLER TEPUNG RUMPUT LAUT (Eucheuma cottoni) - , DEWIANA MENTARI, Dr. Ir. Sri Naruki, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Economically, the decreasing layers are unprofitable, those are classified as chicken afkir and frequently slaughtering to be used the flesh. But the fleshes of chicken afkir produce the gristly fleshes so those have low value. Therefore, the values of chicken afkir need to be improved such as for meatball ingredients. The best meatball ingredient is pre rigor flesh. But it cannot be found at market so time delay process occurs after slaughtering. Tapioca is always poured in meatball production as the filler. Seaweed flour can be the alternative to substitute the tapioca because both produce gel to increase the meatball elasticity. The aim of this research is to find out the influence of time after slaughtering the chicken afkir for the meatball characteristic by seaweed flour filler. First, made the meatball after slaughtering with time variation 1, 3 and 5 hours also use tapioca as the filler. The good time of slaughtering is chosen by the panelist to produce meatball by using tapioca for the filler and flour seaweed. The seaweed flour ratio variation and tapioca in a row are 0:100, 25:75, 50:50, 75:25 and 100:0 %(b/b). The proximate analysis and physical also sensory are used. The result shows the substitute of seaweed flour increasing the water level, protein, grease, ash, and meatball elasticity also decreasing the cooking loss and the meatball appearance. The chicken afkir meatball after slaughtering 3 hours with four seaweed substitution 25% up to 50% can be approved by panelist. Those are based on the Indonesian National Standard, except the water level. Key words: Chicken afkir, chicken afkir meatball, seaweed flour, time after slaughtering